'Always Returning from It': Neoliberal Capitalism, Retrospect, and Marlon James's A Brief History of Seven Killings. Issue 2 (August 2018) - Deckard, Sharae
Abstract : This article contemplates the question of the afterwardly through a reading of Marlon James's A Brief History of Seven Killings (2014). I argue that in Brief History, anxieties about the inability to summon a future beyond the present – to know a world beyond neoliberal capitalism – are formally generative, providing the literary and cultural material for experimentation. Far from having exhausted the potential of the literary, the novel instead insists on the vitality of counter-hegemonic representation of the rise of the neoliberal world-system, and the capacity to resurrect the 'not-known' social totality of an earlier historical event even as it simultaneously struggles to imagine potentialities of collective agency in the present. James constructs a retrospective history of the aftermath of the 1976 attempted assassination of Bob Marley, reinterpreted from the standpoint of the twenty-first century in order to narrate not only the individual traumas incurred by the event, but in order to rematerialise a collective history of the social, systemic, and inter-state violence perpetrated by the neoliberal turn of capitalist accumulation in the Caribbean. In particular, the novel offers a hemispheric view of the complex historical causality of the political destabilisation of Caribbean and Latin American states through CIA-sponsored drug and arms trafficking, the exploitation of extractivist resource regimes, and the economic imposition of structural adjustment programmes.